Galacto-oligosaccharides directly attenuate lipopolysaccharides-induced inflammatory response, oxidative stress and barrier impairment in intestinal epithelium. (April 2022) - Tian, Shiyi; Wang, Jue; Gao, Ren; Wang, Jing; Zhu, Weiyun
Graphical abstract: Highlights: Lipopolysaccharides induce an impaired barrier function, inflammatory cytokines, and ROS release. Galacto-oligosaccharides alleviate the impaired barrier function of lipopolysaccharides-challenged IPEC-J2 cells. Galacto-oligosaccharides inhibited the release of inflammatory cytokines and ROS in lipopolysaccharides-challenged IPEC-J2 cells and piglets. Galacto-oligosaccharides relieve the inflammatory response via NF-κB pathway in lipopolysaccharides-challenged IPEC-J2 cells. Abstract: Recently, the indirect promotion of gut health of piglets by galacto-oligosaccharides (GOS) through regulating gut microbes has been well studied. However, whether the GOS had a direct protective effect on intestinal epithelial cells when occurring inflammatory response should be further studied. In this study, we investigated the effect of GOS on lipopolysaccharides (LPS)-induced inflammation in IPEC-J2 cells and suckling piglets. We discovered that LPS exposure increased paracellular permeability and decreased the expression of tight junction proteins, and caused inflammatory response and oxidative stress. In contrast, GOS relieved LPS-induced barrier damage, inflammation, and oxidative stress. We also found that GOS promoted the expression of tight junction proteins that were decreased by LPS stimulation. GOS inhibited LPS-induced nuclear factor-kappa B phosphorylation, leading to the reduction of proinflammatory cytokine and reactive oxygen species (ROS) generation. These results indicate that GOS have a directly protective effect on intestinal epithelial cells when occurring inflammatory response.